2004
DOI: 10.1093/ajcn/80.3.614
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of cis-9,trans-11 and trans-10,cis-12 conjugated linoleic acid on blood lipids in healthy humans

Abstract: Divergent effects of cis-9,trans-11 CLA and trans-10,cis-12 CLA appear on the blood lipid profile in healthy humans: trans-10,cis-12 CLA increases LDL:HDL cholesterol and total:HDL cholesterol, whereas cis-9,trans-11 CLA decreases them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
186
2
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(215 citation statements)
references
References 26 publications
16
186
2
11
Order By: Relevance
“…According to our analysis, consumption of foods enriched in CLA and CLA supplements has favourable effects on LDL-C level. Some studies, in agreement with our results, showed that a mixture of CLA isomers decreased LDL-C level significantly in healthy adults (12,34,39,41) . Noone et al (23) observed that the daily intake of 3 g CLA supplement (50:50 and 80:20) decreased LDL-C levels non-significantly in CLA groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to our analysis, consumption of foods enriched in CLA and CLA supplements has favourable effects on LDL-C level. Some studies, in agreement with our results, showed that a mixture of CLA isomers decreased LDL-C level significantly in healthy adults (12,34,39,41) . Noone et al (23) observed that the daily intake of 3 g CLA supplement (50:50 and 80:20) decreased LDL-C levels non-significantly in CLA groups.…”
Section: Discussionsupporting
confidence: 92%
“…Mean and standard deviation for TC, HDL-C, LDL-C and TAG before and after placebo or CLA consumption were extracted. Data from the following studies were not extracted: four studies without complete data for analysis (35)(36)(37)(38) , four studies without a placebo group (32,(39)(40)(41) , one study that considered special polymorphisms (PPARγ2, Pro12Ala) of healthy adults (42) , one study done on adolescents (43) and participants of three studies had signs of metabolic syndrome or borderline hyperlipidaemia (44)(45)(46) . Complete information about excluded studies is shown in Fig.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there is no clear dose-response relationship in the relative hyperlipidemic properties of trans-10, cis-12 CLA and hypolipidemic properties of cis-9,trans-11 CLA in humans 24 , suggesting that this influence could be exerted even at low doses 24 . Moreover, in apolipoprotein E knockout mice, supplementation with trans-10,cis-12 CLA had a profound pro-atherogenic effect, whereas cis-9,trans-11 CLA impeded the development of atherosclerosis 64 .…”
Section: Metabolic Effects Of Conjugated Linoleic Acidmentioning
confidence: 99%
“…In humans, Tricon et al (2004) reported that encapsulated RA (0.6-2.4 g/day) decreased the ratio of total cholesterol (TC):high-density lipoprotein (HDL) cholesterol while the 18:2 trans-10, cis-12 isomer had opposite effects. On the other hand, Desroches et al (2005) detected no beneficial metabolic effects of a 10-fold CLA mixture enrichment of butter fat in overweight and obese men.…”
Section: Introductionmentioning
confidence: 99%